Strategi Komunikasi Efektif Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru - Marcha Juliadrianti; Mulyani; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The principal's ability to build effective communication has a major contribution in generating teacher morale. The purpose of this study is to find out the various communication strategies carried out by principals to improve teacher morale. This research uses a qualitative approach through literature study, by reviewing various references that discuss the effectiveness of principal communication and its relation to teacher work motivation. The results showed that open and systematizing communication patterns from principals have a positive influence on teachers' work motivation. Consistent and empathetic communication can create mutual trust and strengthen synergy between individuals in the school environment. In addition, providing positive feedback and appreciation for teachers' performance also plays a role in increasing their productivity. Thus, the principal's ability to establish good communication plays an important role in shaping a supportive and cooperative work culture, which in turn contributes to the growth of teachers' work motivation and the improvement of the quality of education in the school environment.